Factors Affecting Biology Lesson Motivation in Secondary School Students - Regmi, Rabin; Devkota, Balak (The Educator Journal, 2022)
Motivation is a theoretical construct used to explain the initiations, direction, intensity, persistence and quantity of behaviour. It is an important determinant of learning and its outcomes, as expressed in academic performances. The proper study of motivational factors is a prerequisite for students’ effective motivation toward learning. So, a teacher should accept the effect of motivation in the instructional process and should keep knowledge of factors influencing motivation during the learning process. Hence, this study evaluates the factors affecting biology lesson motivation in secondary level students under quantitative research design. The sample of the study was randomly selected 200 students (51.5% girls and 48.5% boys) from grades nine and ten from five government-managed secondary schools. The research data was collected using a questionnaire developed by Glynn and Koballa (2006) as a science lesson motivation questionnaire and adapted by Ekici (2009) as a biology lesson motivation questionnaire. The data were analyzed by applying quantitative procedures using Statistical Program for the Social Sciences. The result generally indicates that students feel biology is an interesting subject with practical value relevant to their lives. Though the students were not confident on their Biology tests and were not receiving grade motivation, they were not greatly worried about the biology tests. Self-determination is the major motivating factor with the highest mean score of 4.170, followed by career motivation (3.890), intrinsic motivation, and personal relevance. Grade motivation has least role in Biology lesson motivation. Moreover, there is a significant correlation (r= 0.592) of intrinsic motivation and personal relevance with self-efficacy and assessment anxiety. There is low correlation between Self-efficacy and assessment anxiety and Self-determination but is significant.